Pengukuran Efektivitas Penyaluran Zakat pada Badan Amil Zakat Nasional Provinsi Bengkulu - Bahri, Efri Syamsul; Utama, Indra (Institut Agama Islam Bengkulu, 2021)
The measurement of Effectivity should be done to describe the capacity of zakat management on distributing zakat fund. This research aims to do the measurement about the zakat effectivity distributed by Badan Amal Zakat Nasional (Baznas) Bengkulu. The effectivity of distribution measured by zakat core principle approach with formula ratio of distribution to collection. Data were taken from Baznas Bengkulu for the period 2016-2019. The result of distributed zakat effectivity level shows that ration ACR 100,16 percent as the highly effective category. The average amount of yearly zakat for the period 2016-2019 is Rp. 3.737.002.758 meanwhile the average amount of yearly zakat is Rp3.742.975.174. Based on the result, Baznas Bengkulu have the sufficient capacity to distribute zakat. Because of that, the result of this reseach is important to encourage Baznas Bengkulu on optimalizing the collection and distribution zakat continously in order to maximize the benefit of zakat for Mustahiq.